CRITICAL PEDAGOGY DIALOGUE AS THE SOLUTION TO K13 QUESTIONING STAGE PROBLEMS IN A VOCATIONAL HIGH SCHOOL IN SURABAYA - FIRDA, (RETAIN : Journal of Research in English Language Teaching, 2015)
Abstract This study shows the application of Critical Pedagogy Dialogue within classroom contexts, especially in a vocational high school, whose objective is to boost the emergence of questions produced by students during the learning process. The aims of this study are: (1) to describe how Critical Pedagogy Dialogue is implemented, and (2) to measure the quality of the questions that the students produced during the learning process. The implementation of Critical Pedagogy Dialogue was implemented by Alexander (2005) and Abrahams (2005) in their experimental researches with whose results concern with Critical Pedagogy Dialogue in early childhood and music education respectively. However, this study is descriptive qualitative in nature. It took place in SMK Negeri 1 Surabaya with the English teacher and the students of X Office Administration 4 class as the subjects. How the teacher followed the style of Critical Pedagogy Dialogue in the classroom was observed in three time observations using field notes to answer the first research question. Meanwhile, the students’ questions were noted on the researcher-generated log and rated using the modified rubric to answer the second question. The result shows that the teacher initiated most characteristics of Critical Pedagogy Dialogue and followed the adapted steps. Furthermore, the students’ questions range from A- to A level questions meaning that they are within the highest quality of enquiring question criteria. Keywords: K13, Questioning Stage, Critical Pedagogy Dialogue, Enquiring Questions Abstrak Penelitian ini mengungkap penggunaan Dialog Pedagogis Kritis dalam konteks kelas, terutama yang ada di SMK, untuk mendorong munculnya pertanyaan yang diciptakan siswa selama proses pembelajaran. Tujuan penelitian ini adalah: (1) untuk mendeskripsikan bagaimana Dialog Pedagogis Kritis diimplementasikan dalam tahap mempertanyakan K13, dan (2) untuk mengukur kualitas pertanyaan yang dibuat siswa selama Dialog Pedagogis Kritis diimplementasikan. Penelitian ini menggunakan penelitian deskriptif kualitatif sebagai desain penelitian. Penelitian ini dilakukan di SMK Negeri 1 Surabaya dengan guru Bahasa Inggris dan para siswa kelas X Administrasi Perkantoran 4 sebagai subyeknya. Cara guru menjalankan kelas dengan mengaplikasikan Dialog Pedagogis Kritis diamati dalam tiga hari observasi dengan menggunakan catatan penelitian untuk menjawab pertanyaan penelitian pertama. Sementara itu, pertanyaan yang diproduksi para siswa dicatat dalam catatan pertanyaan yang dibuat sendiri oleh peneliti. Pertanyaan-pertanyaan tersebut juga diukur dengan menggunakan rubrik buatan peneliti untuk menjawab pertanyaan penelitian kedua. Hasil penelitian ini menunjukkan bahwa guru membawa serta sebagian besar karakteristik seorang guru yang menggunakan Dialog Pedagogis Kritis dan menjalankan kelas berdasarkan langkah-langkah yang telah diadaptasi dan diintegrasikan dengan K13. Selain itu, pertanyaan yang diproduksi para siswa selama implementasi teknik tersebut berada dalam jangkauan pertanyaan tingkat A- sampai A, berarti pertanyaan-pertanyaan tersebut meraih kualitas tertinggi dari kriteria pertanyaan penyelidikan. Kata Kunci: K13, Tahap Mempertanyakan, Dialog Pedagogis Kritis, Pertanyaan Penyelidikan